Targeting ERBB3 and AKT to overcome adaptive resistance in EML4-ALK-driven non-small cell lung cancer - Josephina Sampson; Hyun-min Ju; Nan Zhang; Sharon Yeoh; Jene Choi; Richard Bayliss (Cell Death and Disease)
Abstract The fusion event between EML4 and ALK drives a significant oncogenic activity in 5% of non-small cell lung cancer (NSCLC). Even though potent ALK-tyrosine kinase inhibitors (ALK-TKIs) are successfully used for the treatment of EML4-ALK-positive NSCLC patients, a subset of those patients eventually acquire resistance during their therapy. Here, we investigate the kinase responses in EML4-ALK V1 and V3-harbouring NSCLC cancer cells after acute inhibition with ALK TKI, lorlatinib (LOR). Using phosphopeptide chip array and upstream kinase prediction analysis, we identified a group of phosphorylated tyrosine peptides including ERBB and AKT proteins that are upregulated upon ALK-TKI treatment in EML4-ALK-positive NSCLC cell lines. Dual inhibition of ALK and ERBB receptors or AKT disrupts RAS/MAPK and AKT/PI3K signalling pathways, and enhances apoptosis in EML4-ALK + NSCLC cancer cells. Heregulin, an ERBB3 ligand, differentially modulates the sensitivity of EML4-ALK cell lines to ALK inhibitors. We found that EML4-ALK cells made resistant to LOR are sensitive to inhibition of ERBB and AKT. These findings emphasize the important roles of AKT and ERBB3 to regulate signalling after acute LOR treatment, identifying them as potential targets that may be beneficial to prevent adaptive resistance to EML4-ALK-targeted therapies in NSCLC.